ISSN: 1693-9050 E-ISSN: 2623-1417 https://jurnal.polsri.ac.id/index.php/kimia/index 55 PROTOTIPE BATERAI BERBASIS KARBON AKTIF DARI BAMBU BETUNG (TINJAUAN PENGARUH KARBON AKTIF DAN ELEKTROLIT DALAM MENINGKATKAN DAYA BATERAI) - Pahlevi, Muhammad Agmerio; Junaidi, Robert; HC, Fadarina (KINETIKA, 2020)
Battery is a storage technology electrical energy used for laptops, digital cameras, and cell phones, which are examples of applications that use battery performance. Battery performance involves the transfer of electrons which are conductive. Electron transfer become from the negative electrode (anode) to the positive electrode (cathode), resulting in an electric current and a potential difference. In general the battery system can be classified into two types, that are primary battery system and the secondary battery system. In this research, we use bamboo betung (Dendrocalamus asper) as activated carbon with electrolytes NaCL and NaOH. First, Bamboo Betung which will be carbonized at 500 oC for 2 hours in this furnace is intended to get the best pore for SEM analysis and to increase porosity, the largest measurement result of activated carbon pores is 11.42 Î¼m with 12% KOH activation. Then, the activation was carried out with 1 M KOH with a concentration of 10-12%, then the electrolytes selected were NaOH and 1 M NaCl as much as 5-15 ml. Measurement of voltage and current obtained the smallest power obtained in the measurement of activated carbon 10% KOH with 5 ml NaCL electrolyte of 7.5036 mWatt. The greatest power was obtained in the measurement of activated carbon activated by 12% KOH with 15 ml NaOH electrolyte 103.0336 mWatt.